Harold Edwin Hurst: the Nile and Egypt, past and future. Issue 9 (3rd July 2016) - Sutcliffe, John; Hurst, Stephen; Awadallah, Ayman G.; Brown, Emma; Hamed, Khaled
ABSTRACT: H.E. Hurst spent some 60 years studying the Nile for the Egyptian government, and laid the foundation for a monumental set of hydrological records and investigations. His studies of the size of over-year reservoirs needed to maintain a given yield from Nile flows showed that this was greater than that based on random series. This finding, known as the Hurst phenomenon, was confirmed by other natural series and led to important advances in practical and theoretical statistics. His work led to the design of the Aswan High Dam and to continued research in Egypt.Editor D. Koutsoyiannis;Guest editor E. Eris